Home Testing May Not Improve Postvasectomy Semen Analysis Compliance. Issue 3 (4th May 2021) - Punjani, Nahid; Andrusier, Miriam; Hayden, Russell; Dudley, Vanessa; Matos-Vargas, Eliana; Goldstein, Marc
Abstract: Introduction: Vasectomy is the most effective form of permanent male contraception. Although vasectomy techniques and outcomes have steadily improved, postvasectomy semen analysis compliance remains a significant challenge. The aim of this study was to assess if home testing improved postvasectomy semen analysis compliance. Methods: Data were collected prospectively but retrospectively reviewed between 2007 and 2019 from a single surgeon's high volume practice. Subjects were divided into 2 groups based on postvasectomy semen analysis method (home vs office) and further subdivided by compliance status. Patients were considered compliant if they provided at least 1 semen sample postvasectomy. Statistical analysis was completed to determine factors predictive of compliance. Results: A total of 364 patients were included. Median age for the home group vs the office group was similar (42 years [IQR 39–46] vs 41 years [IQR 38–46]). Median number of children for both groups was 2 (IQR 2–3). In all, 109 men (30.0%) opted for at-home testing. No significant difference in compliance was found (59.6% of home test vs 58.8% of laboratory patients, p=0.89). No statistically significant difference in patient demographics (age, partner age, number of children, smoking and alcohol) was observed, and there were no demographic factors predicting compliance with regression modeling. Conclusions: At-home semen analysis kits did not significantly improve compliance. Clinicians should be aware that this may be a reasonable alternative for those who are unable to obtain a postvasectomy semen analysis in-office. Contact of the female partner instead may improve postvasectomy semen analysis compliance as the female partner has a stake in ensuring postvasectomy semen analysis azoospermia.